ITS amplicon sequencing revealed that rare taxa of tea rhizosphere fungi are closely related to the environment and provide feedback on tea tree diseases - Yuanqi Zhao; Weiwei Ran; Wenming Xu; Yuehua Song (Microbiology Spectrum)
ABSTRACT The rhizospheres of plants and soil microorganisms are intricately interconnected. Tea trees are cultivated extensively on the karst plateau of Guizhou Province, China; however, the understanding of the interactions among fungal communities, community taxa, and diseases impacting tea tree in the soil rhizosphere is limited. Our aim is to offer insights for the advancement of modern agriculture in ecologically fragile karst tea gardens, as well as microbiomics concepts for green and sustainable environmental development. This study utilized the internal transcribed spacer high-throughput sequencing technology to explore the symbiotic relationship between rhizosphere fungi and plant disease feedback in multiple tea estates across the Guizhou Plateau. The ecological preferences and environmental thresholds of fungi were investigated via environmental variables. Furthermore, a correlation was established between different taxa and individual soil functions. Research has indicated that tea leaf blight disrupts symbiotic connections among fungal groups. For various taxa, we found that numerous taxa consistently maintained core positions within the community, whereas rare taxa were able to stabilize due to a high proportion of positive effects. Additionally, abundant taxa presented a wider range of environmental feedback, whereas the rare taxon diversity presented a stronger positive association with the soil Z score. This study contributes to our understanding of the importance of rare taxa in plant rhizosphere soil processes. Emphasis should be placed on the role of rare taxa in pest and disease control within green agriculture while also strengthening systematic development and biogeographical research related to rare taxa in this region.IMPORTANCEIn this study, based on internal transcribed spacer high-throughput sequencing, fungal communities in the rhizosphere soil of tea trees and their interactions with the environment in karst areas were reported, and the symbiotic relationships of different fungal taxa and their feedback to the environment were described in detail by using the knowledge of microbial ecology. On this basis, it was found that tea tree diseases affect the symbiotic relationships of fungal taxa. At the same time, we found that rare taxa have stronger cooperative relationships in response to environmental changes and explored their participation in soil processes based on fungal trait sets. This study will provide basic data for the development of modern agriculture in tea gardens and theoretical basis for the sustainable prevention and control of tea tree diseases.